Factors that influence employee engagement in organizations / Nur Aqilah Mohamad Yusop - Mohamad Yusop, Nur Aqilah (2014)
The purpose of the study is to investigate the relationship between job satisfaction and work life balance with employee engagement. The objectives of this study are to find out the relationship between job satisfaction with employee engagement and also the relationship between work life balance with employee engagement in organizations. This study was used questionnaire as instrument to gain the data. The questionnaire is personally administrated distribute to 100 respondents around Malacca and Selangor. The respondents are from various company and job positions. Pearson Correlation is conducted to find out the relationship between job satisfaction and work life balance with employee engagement. Multiple regressions are applied to find out the most influencing factor of employee engagement. The study was found that there are positive relationship between job satisfaction and work life balance with employee engagement. The study also found that job satisfaction is the factor that most influencing employee engagement.